PERANCANGAN PROTOTYPE PENGENDALIAN SMART LAMP BERBASIS ARDUINO PADA KECAMATAN WELERI - Azani Fajri, Laksamana Rajendra Haidar; Muthohir, Moh; Balya Balya (CV. Denasya Smart Publisher, 2024)
The aim of this research is to produce real results in providing comfort or convenience in turning on or off night life in everyday homes, especially for people who forget to turn off the lights. The method used in making microcontroller-based home lighting control using an Android smartphone is. This research method consists of several stages, analysis method, design method, implementation testing method, and maintenance. The results achieved are improving aspects of comfort and convenience for agencies, where this series of tools works after Bluetooth devices are available on Android smartphones. connected to a bluetooth module connected to an arduino microcontroller. Basically, the principle of using this tool is that users must be able to operate a smartphone based on the Android operating system. The conclusion is that this equipment has been tested and can be used as an Android smartphone light controller via Bluetooth connection without having to press the light button